Heart rate variability and vagal tone in schizophrenia: A review. (October 2015) - Montaquila, Julian M.; Trachik, Benjamin J.; Bedwell, Jeffrey S.
Abstract: Recent heart rate variability (HRV) research has identified diminished levels of parasympathetic activity among schizophrenia patients. Over two dozen empirically-based studies have been published on this topic; primarily over the last decade. However, no theoretical review appears to have been published on this work. Further, only one empirical study has evaluated HRV research findings in the context of documented hypothalamic-pituitary-adrenal axis hyperactivity in schizophrenia. HRV research indicates that no abnormalities exist in the initial sympathetic stress response of schizophrenia patients. However, evidence has consistently demonstrated that patients exhibit a diminished capacity to recover from a stress response as a result of deficits in parasympathetic activity. Moreover, this diminished parasympathetic nervous system (PNS) response, also known as decreased vagal tone, has been found to relate to increased symptom severity. Although these findings may cause speculation that the observed vagal tone disruption merely results from anxiety produced by the presence of positive symptomology, additional studies have identified similar parasympathetic dysfunction among nonpsychotic relatives of individuals with schizophrenia. We posit that the resulting sympathovagal imbalance leads to an overall sympathetic dominance despite the fact that sympathetic nervous system activity is not abnormally elevated among patients. Implications are discussed within the context of the diathesis-stress/vulnerability-stress model, including the potential for identifying a mechanism of action by which environmental stressors may contribute to triggering first-episode psychosis. Highlights: Vagal tone deficits in schizophrenia are accompanied by sympathetic dominance. Unopposed sympathetic activity leads to a protracted stress response in patients. A similar protracted stress response is found in patients' first-degree relatives. Symptom severity and heart rate variability appear to be negatively correlated. Hypothalamic-pituitary-adrenal and heart rate variability data are complementary.